Kombinasi Chewing Gum dan Early Mobilization Terhadap Peningkatan Peristaltik Usus dan Flatus pada Pasien Post SC di RS Bhayangkara Jambi - Sari, Yulia Indah Permata; Ekawaty, Fadliyana; Mutmainnah, Muthia; Martawinarti, Rts Netisa (Jurnal Akademika Baiturrahim Jambi, 2025)
Anesthesia given to patients undergoing cesarean section can slow down gastrointestinal motility because it impedes nerve stimulation for peristalsis, leading to effects such as abdominal distension and even paralytic ileus. Several strategies and non-pharmacological interventions can be applied to enhance intestinal peristalsis, such as chewing gum to stimulate intestinal motility through the cephalic-vagal reflex, and early mobilization, which helps restore circulation more quickly, thus ensuring that the body's nutritional and oxygen needs are met. The urgency of this study lies in the combination of chewing gum and early mobilization as nursing interventions that simultaneously stimulate parasympathetic nerves to the intestinal muscles. The aim of this study is to assess the effect of combining chewing gum and early mobilization on the improvement of intestinal peristalsis and flatus in post-cesarean section patients. This study uses a quasi-experimental design with a one-group pre-post test design approach. The sample in this study consisted of 50 cesarean section patients, with a non-probability sampling technique using consecutive sampling from patients undergoing cesarean surgery at Bhayangkara Hospital in Jambi. Data were collected using demographic questionnaires and checklists. The analysis using the paired t-test showed significant results (p < 0.05), indicating that the combination of chewing gum and early mobilization has an effect on increasing intestinal peristalsis and accelerating the first passage of flatus. The results of this study indicate that the combination of chewing gum and early mobilization leads to waves of intestinal motility, with an increase in parasympathetic nerve activity causing the release of acetylcholine, which in turn enhances the conduction of peristaltic waves along the intestinal wall, thereby improving intestinal motility and accelerating the time to first flatus. It is recommended that nurses implement these interventions to enhance intestinal peristalsis and accelerate the time to first flatus after a cesarean section.